Leveraging eBPF/XDP for Real-Time Machine Learning Traffic Classification in 5G User Plane Networks - Galvão, José Silvestre da Silva; Rocha, Flávio Geraldo Coelho; Gomes, Ruan Delgado; Almeida, Leandro C. de (Anais do Workshop de Inteligência Artificial para Redes de Computadores (WIARC); 2026: Anais do I Workshop de Inteligência Artificial para Redes de Computadores, 2026)
5G networks impose stringent requirements, such as low latency and high throughput, that challenge traditional traffic classification mechanisms within the UPF. These approaches often become bottlenecks due to the overhead and latency of user-space processing. To address the challenges, this work proposes a methodology for real-time traffic classification using In-Kernel Machine Learning with eBPF/XDP. The implementation employs C headers and leverages native eBPF mechanisms to manage verifier constraints. Experimental results demonstrate that In-Kernel ML significantly outperforms user space execution, achieving over 36× faster inference speed, reduced CPU usage from 15.79% to 12.87%, and maintaining 99.91% of accuracy.